Corporeality: from the Figure to the Text Structure (O. Tokarczuk's Flights) - Skikaitė, Izabelė (Semiotika, 2023)
Olga Tokarczuk’s fragmented novel Flights (Bieguni, 2007) encompasses various genres and themes that distinguish corporeality. Its analysis reveals how a corporeal isotopy of the content plane explains the expression plane, i.e., the novel’s composition. Therefore, this article contributes to the marginally explored research field in the semiotics of literature – the interaction between content semantics and poetics. In the novel, not only can various forms of the human body be found – such as bodies engaged in different modes of travel, sick bodies, and body specimens – but also contrasting corporeal ideologies that elucidate the connection between different fragments of the book. The article describes the novel‘s characters – pilgrims, runaways, and anatomists – and their relationship with movement and the body, revealing their worldview. Moreover, it solves the problem of matching the opposite conceptions of the body, the phenomenological and the mechanical, and addresses how the opposing characters’ attitudes can be integrated into the text’s semantic universe. The axiology of the protagonists is expressed by the category of integrity/disintegration. This, along with the corporeal relationships that repeat in different stories, discloses that Tokarczuk’s text functions as a particular body. Furthermore, it suggests a specific conception of the literary text.
Keywords: Tokarczuk; Flights; body; semiotic square